Deep Domain Adaptation, Pseudo-Labeling, and Shallow Network for Accurate and Fast Gait Prediction of Unlabeled Datasets - Jaeyoung Na; Hyunwoo Kim; Giuk Lee; Woochul Nam (IEEE, 2023)
Developing personalized gait phase prediction models is difficult because acquiring accurate gait phases requires expensive experiments. This problem can be addressed via semi-supervised domain adaptation (DA), which minimizes the discrepancy between the source and target subject features. However, classical DA models have a trade-off between accuracy and inference speed. Whereas deep DA models provide accurate prediction results with a slow inference speed, shallow DA models produce less accurate results with a fast inference speed. To achieve both high accuracy and fast inference, a dual-stage DA framework is proposed in this study. The first stage uses a deep network for precise DA. Then, a pseudo-gait-phase label of the target subject is obtained using the first-stage model. In the second stage, a shallow but fast network is trained using the pseudo-label. Because computation for DA is not conducted in the second stage, an accurate prediction can be accomplished even with the shallow network. Test results show that the proposed DA framework reduces the prediction error by 1.04% compared with a shallow DA model while maintaining its fast inference speed. The proposed DA framework can be used to provide fast personalized gait prediction models for real-time control systems such as wearable robots.